The Effect of DRTA Teaching Strategy and Learning Style on Students’ Achievement in Reading Comprehension at Faculty of Tarbiyah Science and Teacher Training State Islamic University of North Sumatra - Yani Lubis (VISION, 2018)
The objectives of this study were to examine whether (1) the DRTA Strategy can effect on students’ achievement in reading comprehension or not, (2) the achievement in reading comprehension of the students with extrovert learning style is higher than introvert learning style if they taught by DRTA strategy, (3) there is no interaction between DRTA strategy and Learning Styles on the students’ achievement in reading comprehension. It was an experimental research with factorial design 2x2. The data were analyzed by using two-way ANOVA by using SPSS program. After the data had been calculated, it is found that (1) DRTA strategy has affect students’ achievement in reading comprehension (Sig. = 0.026<0.05), students’ achievement in reading comprehension taught by DRTA strategy is (76.10). (2) the achievement in reading comprehension of the students with Extrovert learning style is higher than the students with Introvert learning style (83.64>73.80) and (3) there is no  interaction between teaching strategies and Learning Style if they combined on the students’ achievement in reading comprehension (Sig. = 0.658 > 0.05).Key Word:     DRTA Teaching Strategy; Learning Style; Students’ Achievement